The right-wing populism of India's Bharatiya Janata Party (and why comparativists should care). Issue 3 (3rd April 2019) - McDonnell, Duncan; Cabrera, Luis
ABSTRACT: Despite the vast amount of comparative research on right-wing populist parties over the past decade, there has been little work on non-European parties (as opposed to leaders). In this article, we argue that the international literature on populist parties has largely overlooked a significant non-European case: India's ruling Bharatiya Janata Party (BJP – Indian People's Party). Following the ideational approach to understanding populism, we examine whether the three distinguishing features of right-wing populism – its conceptions of "the people", "elites" and "others" – are reflected in the views from interviews we conducted with BJP officials and representatives. We find that they are and so then consider whether they have been manifest in actions and statements while in power or whether, as some scholars claim, governing parties like the BJP moderate their populism. We conclude that the BJP can be very fruitfully included in comparative research on right-wing populist parties and propose a series of concrete ways in which this could be pursued.